CORRELATIONS OF BODY STRUCTURE AND SIZE PARAMETERS WITH PERSONALITY INDICATORS OF PRACTICALLY HEALTHY WOMEN WITH ECTOMORPHIC SOMATOTYPE - Andriievskyi, I.I.; Serebrennikova, О.А.; Shayuk, A.V.; Kovalchuk, V.V.; Likhitskyi, O.O. (World of Medicine and Biology, 2021)
In practically healthy Ukrainian women of ectomorphic somatotype, multiple, mostly of medium-strength correlation of Shmishek character accentuation indices with the majority of head size and transverse body size and half the girth body size have been established; as well as scales of general internality, the level of subjective control, the level of subjective control in the field of achievement, in the field of family relations, in the field of educational (professional) relations and in the field of health and disease according to Rotter with most longitudinal, girth body sizes and indicators of the of skinfold thickness. Multiple medium strength correlations are established for cyclothymic, excitatory, and exalted accentuations character type by Shmishek with most longitudinal body sizes.
Keywords: correlations; healthy women of ectomorphic somatotype; personality indicators; anthropo-somatotypological indices